2018
DOI: 10.1177/0018720818769261
|View full text |Cite
|
Sign up to set email alerts
|

Muscular and Vascular Issues Induced by Prolonged Standing With Different Work–Rest Cycles With Active or Passive Breaks

Abstract: Prolonged standing is likely to contribute to musculoskeletal and vascular symptoms. A limitation to less than 3 hr of mostly static standing in occupational activities could avoid alterations leading to these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 80 publications
9
27
0
2
Order By: Relevance
“…These expected effects conform to previous results showing that prolonged standing induce long-lasting muscle fatigue (Garcia et al, 2015(Garcia et al, , 2016(Garcia et al, , 2018Wall et al, 2020), edema Antle et al, 2018;Garcia et al, 2018;Hansen et al, 1998;Wall et al, 2020;Zander et al, 2004), and discomfort (Garcia et al, 2015(Garcia et al, , 2018, Drury et al, 2008. However, in this field study, lower-leg muscle fatigue and edema were not yet significant after 6 hr of standing work, when wearing regular socks, while these effects were seen to appear within 3 hr of static standing work at an office workstation Garcia et al, 2015Garcia et al, , 2016Garcia et al, , 2018Wall et al, 2020). In this latter condition, lowerleg muscle fatigue was strongly present after 3 hr of light manual work including various rest break distributions (Garcia et al, 2015(Garcia et al, , 2016(Garcia et al, , 2018 regardless of age, gender, and habituation to standing work (Garcia et al, 2015;Wall et al, 2020); hence, these factors are not considered in the present work.…”
Section: Prolonged Standing With Regular Sockssupporting
confidence: 91%
See 1 more Smart Citation
“…These expected effects conform to previous results showing that prolonged standing induce long-lasting muscle fatigue (Garcia et al, 2015(Garcia et al, , 2016(Garcia et al, , 2018Wall et al, 2020), edema Antle et al, 2018;Garcia et al, 2018;Hansen et al, 1998;Wall et al, 2020;Zander et al, 2004), and discomfort (Garcia et al, 2015(Garcia et al, , 2018, Drury et al, 2008. However, in this field study, lower-leg muscle fatigue and edema were not yet significant after 6 hr of standing work, when wearing regular socks, while these effects were seen to appear within 3 hr of static standing work at an office workstation Garcia et al, 2015Garcia et al, , 2016Garcia et al, , 2018Wall et al, 2020). In this latter condition, lowerleg muscle fatigue was strongly present after 3 hr of light manual work including various rest break distributions (Garcia et al, 2015(Garcia et al, , 2016(Garcia et al, , 2018 regardless of age, gender, and habituation to standing work (Garcia et al, 2015;Wall et al, 2020); hence, these factors are not considered in the present work.…”
Section: Prolonged Standing With Regular Sockssupporting
confidence: 91%
“…Lower-leg volume. This metric was obtained through a volumetric edema gage (ProHealthcareProducts, USA) as described in our previous studies (Garcia et al, 2018(Garcia et al, , 2020. The participants were asked to sit in an upright position and insert slowly their left lower leg in a tank filled with warm water until resting their foot on the floor with 90° knee and ankle angles.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Because only one high-quality RCT evaluated the combination of posture variation and a rest break and this study found no effect, there is limited evidence of no effect. Garcia, Lubli, and Martin (2018) assessed the duration and amplitude of muscle twitch force during a 5-hr simulated standing work with work–rest cycles with short, medium, or long standing periods including passive or active breaks. No significant differences in fatigue outcomes in the lower extremities were found between conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Stresorji zaposlenih v zdravstveni negi se močno razlikujejo glede na zahtevnost delovnega mesta (Henrich, et al, 2017). Pomemben dejavnik stresa zaposlenih v zdravstveni negi je izmensko delo (Zhang, et al, 2017;Kagamiyama & Yano, 2018), zato je izjemnega pomena zadosten čas počitka po končanem delavniku (Tsuchiya, et al, 2017;Bae, et al, 2018;Garcia, et al, 2018). Počitek je zaradi dela, ki presega delovni čas, lahko skrajšan.…”
Section: Uvodunclassified